Intestinal and hepatic benefits of BBR-EVO on DSS-induced experimental colitis in mice - Wang, Wenjia; Han, Yiheng; Yin, Wen; Wang, Qiaozhi; Wu, Yi; Du, Maobo (Frontiers in Microbiology, 2024)
Ulcerative colitis (UC), characterized by disrupted intestinal barrier integrity and chronic inflammation, was modeled in mice via dextran sulfate sodium (DSS) induction. This study explored the therapeutic potential of berberine-evodiamine (BBR-EVO), bioactive components of the traditional Chinese medicine Yulian decoction, in DSS colitis. BBR-EVO intervention ameliorated weight loss, diarrhea, colonic shortening, and histopathological damage in colitic mice. The substance increased antioxidant activity while reducing high levels of pro-inflammatory cytokines in the colon, including as TNF-α, IL-1β, and IL-6. BBR-EVO inhibited the DSS-induced decrease in the tight junction proteins ZO-1 and occludin, according to immunohistochemistry. 16S rRNA sequencing demonstrated BBR-EVO partially attenuated DSS-elicited intestinal dysbiosis, reducing opportunistic pathogens and restoring diminished beneficial taxa. Critically, BBR-EVO alleviated secondary hepatic injury in colitic mice, mitigating immune cell infiltration, oxidative stress, cytokine production, and ultrastructural damage, likely by beneficially modulating gut-liver crosstalk. This study reveals BBR-EVO, derived from a traditional Chinese medicine, confers multi-target protective effects in experimental colitis and associated hepatic pathology, warranting further evaluation as a potential therapy for inflammatory bowel diseases like UC. The mechanisms may involve simultaneous augmentation of intestinal barrier integrity, inhibition of inflammation, microbiota regulation, and gut-liver axis optimization.